The Role of Information Technology in Increasing the Effectiveness of Taxation at the Jakarta Kemayoran Pratama Tax Service Office - Prastiwi, Mela (Indonesian Scientific Publication, 2023)
This study discusses the effectiveness of the use of Information Technology in improving the tax system at the Tax Office pratama jakarta kemayoran. The purpose of this study was to analyze the effectiveness of the use of Information Technology in improvin g the tax system at the Tax Office Pratama Jakarta Kemayoran, analyze the entity inhibiting the effectiveness of the use of Information Technology in improving the tax system at the Tax Office Pratama Jakarta Kemayoran and analyze the entity driving the effectiveness of the use of Information Technology in improving the tax system at the Tax Office Pratama Jakarta Kemayoran. The research methods used for this study are descriptive qualitative. Data collection using observation, interviews, and documentation. The results of this research for KPP Pratama Jakarta Kemayoran prepare the availability of computer units in accordance with service needs. It can be said that the effectiveness of the service is due to the availability of 7 units of computers and can be used by wp itself. the system and mechanism of taxpayer database storage is very confidential and only located at the DGT headquarters. to improve the effectiveness of taxation using several programs, software, and applications including: service TPT program, tax amnesty program, voluntary disclosure program (PPS), etc. The obstacles faced are from the taxation of this online system, because there are still taxpayers who do not understand the online system of taxation from the way it operates so that it can take time to learn things related to taxation. Efforts that can be done is to continue to improve performance, especially in terms of delivering comprehensive education and socialization so that taxpayers can know well the latest information, especially taxation.